An Intramolecular Ene Reaction of a Chiral Bicyclic Lactam1 - Resek, James E. (2008)
[Image: see text] The preparation of bicylic lactam 2 is described, employing an acetoacetate-based synthesis of 1,4-ketoacid 3. The lactam 2 was shown to undergo a thermal ene reaction at 280–300 °C to afford tricycle 7. Reduction of the ene product followed by removal of the chiral auxiliary fragment provided the unusual lactam system 9 in highly enantioenriched form.